The effectiveness of the chop tackle in elite and semi-professional rugby union - Evans, L.; O'Donoghue, P. (International Journal of Performance Analysis in Sport, 2013)
The aim of this study was to analysis tackles within 2 levels of rugby union. Ten Rugby World Cup matches and 10 Principality Welsh Premiership matches were analysed. The 125.8±40.6 tackles performed in World Cup matches was significantly greater than the 88.1±14.0 performed in Welsh Premier matches.